(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
Abstract This study contains about the application of Undang-Undang Number 2 of 2012 concerning Procurement of Land for Development for Public Interest. Development for public interest in this case is the Paselloreng Dam which is located in Gilireng District, Wajo Regency, South Sulawesi. The Wajo Regency Government has collaborated with the Public Appraisal Service to determine the compensation price for land owned by the people. On the other side, some Paselloreng people were not satisfied with the compensation price for land that had been determined and filed a lawsuit against the local government. The results of this study indicate that the process of implementing compensation for land is in accordance with the applicable regulations and the price set by the government through Public Appraisal Services above the Sales Value of the Tax Object. The form of people rejection of the compensation value is to sue the executing committee for land acquisition because no agreement was found between the two parties after mediation by the government as the facilitator. The Sengkang District Court has rejected the applicant& claim in this case the Paselloreng people. However, the petitioner has filed an appeal to the Supreme Court and the lawsuit is still on going. Abstrak Penelitian ini memuat tentang penerapan Undang-Undang Nomor 2 tahun 2012 tentang Pengadaan Tanah Bagi Pembangunan Untuk Kepentingan Umum. Pembangunan untuk kepentingan umum dalam hal ini adalah Bendungan Paselloreng yang terletak di Kecamatan Gilireng, Kabupaten Wajo, Sulawesi Selatan. Pemerintah Kabupaten Wajo telah bekerja sama dengan Jasa Peniilai Publik untuk menetapkan harga ganti rugi atas tanah milik masyarakat. Di lain pihak, beberapa masyarakat Paselloreng merasa kurang puas dengan harga ganti rugi atas tanah yang telah ditetapkan dan melakukan gugatan terhadap pemerintah setempat. Hasil penelitian ini menunjukkan bahwa proses pelaksanaan ganti rugi atas tanah telah sesuai dengan aturan yang berlaku dan harga yang telah ditetapkan pemerintah melalui Jasa Penilai Publik diatas dari Nilai Jual Obyek Pajak. Bentuk penolakan masayarakat terhadap nilai ganti rugi tersebut ialah dengan menggugat panitia pelaksana pengadaan tanah karena tidak ditemukan kesepakatan antara kedua belah pihak setelah dilakukan mediasi oleh pemerintah selaku fasilitator. Pengadilan Negeri Sengkang telah menolak gugutan pemohon dalam hal ini masyarakat Paselloreng. Namun, pemohon telah ini proses gugutan masih berlangsung.